5 - The African Public Space of Dangarembga’s Neria: A Site for Autochthonous Feminist Agency - Kapasula, Jessie Kabwila (Africa Development, 2021)
The public space is a place where anybody has a right to occupy without being excluded for economic or social reasons. This paper is an attempt to illustrate the ‘westocentricity’ and inapplicability of the term ‘public space’ to the African context. This term is steeped in the discourse of capital, one that profits from proliferating labels like ‘public’, ‘free’, ‘open’, masquerading in appearances that gloss over the hegemonic forces like global patriarchy, capitalism and neo-colonialism that largely govern twenty-first century Africa. An interrogation of the spaces that can be called the ‘commons’ in Dangarembga’s Neria (1986) and Nervous Conditions (1988), (Zimbabwe) and Sene Absa’s Madame Brouette (2002) (Senegal), shows that such spaces are fraught with social constraints that discriminate against access at class and gender levels, just to mention a few. I will illustrate how language constrains poor and illiterate Africans, especially women, from accessing places such as the river, and legal and entertainment public spaces in the literary works outlined above. It is important for scholarship on Africa to emphasize that ‘The African public space’ is an oxymoron, a fallacy that does not exist. There is no space that can legitimately be called ‘public’ in Africa, especially for rural, poor, uneducated, non-Christian/Muslim women.